2019
DOI: 10.3390/ma12213617
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and Compressive Strength of Steel Fiber Reinforced MgO Concrete

Abstract: To reduce the cracking caused by shrinkage and avoid the brittle behavior of concrete, MgO expansion agent and steel fibers were used in this paper. Firstly, the effect of MgO and steel fibers on the compressive strength of concrete was compared. The results showed that the compressive strength of steel fibers reinforced concrete (SC) and steel fiber reinforced MgO concrete (SMC) was significantly improved. Compared with ordinary concrete (OC), SMC’s 28 days compressive strength increased by 19.8%. Secondly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Steel fiber is one of the most popularly used fibers to enhance the mechanical strength of concrete [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Nguyen et al indicated that the effects of rubber aggregates and fiber reinforcement could result in better cracking resistance for cement mortar [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steel fiber is one of the most popularly used fibers to enhance the mechanical strength of concrete [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Nguyen et al indicated that the effects of rubber aggregates and fiber reinforcement could result in better cracking resistance for cement mortar [28].…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen et al indicated that the effects of rubber aggregates and fiber reinforcement could result in better cracking resistance for cement mortar [28]. Jiang et al pointed out that the constraint effect of steel fiber improved the interfacial bond strength of concrete [29]. Zhang et al concluded that the incorporation of steel fiber enhanced the freezing-thawing resistance and cracking resistance of concrete containing nano-particles [30].…”
Section: Introductionmentioning
confidence: 99%
“…No expansion of the samples was observed at any time. The reached value of about 0.5 mm/m and almost the same for both types of concretes is typical for concretes containing these amounts of cement [ 35 , 62 ].…”
Section: Resultsmentioning
confidence: 79%
“…The three-dimensional distribution of steel fiber seriously restricts the expansion of MgO, changes the expansion mode of MgO, and makes the expansion from outward extension to inward extrusion, which greatly improves the compactness of SFRMC. Our previous research [21] has confirmed that SFRMC has excellent mechanical properties, but its durability has not been studied. In this paper, split tensile test, chloride diffusion test, mercury intrusion porosimeter MIP test, and scanning electron microscopy SEM test were conducted to study the combined effect of steel fiber and MgO on the tensile strength and chloride diffusion resistance of SFRMC.…”
Section: Introductionmentioning
confidence: 96%